Outer sunset : a novel - Pothier, Mark Ernest, 1959- (University of Iowa Press, 2023)
"Jim Finley - a recently retired English teacher living alone on the shifting edge of San Francisco - has been set, unwittingly, on the back porch of life. Trying to harmonize the voices in his head, he sits most days by his stack of "to-do" books until, one day, his daughter comes home with the worst news of her life. Everything changes - it must - and as his broken heart reengages, he steps back into a new world. He sees his ex-wife has launched into a larger life than the one they'd shared. He is surprised to find it easier to talk to his son's immigrant girlfriend, or even the incorrupt remains of a Russian saint, than to the young man he's raised. He misconnects with Carol, his first date in decades - a woman he enjoys talking to but doesn't quite hear. And he learns he must struggle more every day to keep from losing his daughter, and life's sweetness. Set in the temporary, pre-tech calm before the turn of this century, Outer Sunset is a deeply felt story about the intimate place where long-lasting growth occurs in our lives. It is a novel about how to revise, or live without, your dreams; how to love the flaws of those closest to you and watch a child grow away into someone better than you'd imagined; and about how to be shaken by beauty amidst unimaginable loss and remain standing"--